Production and processing of polymer-based nanocomposites - Hilliou, L. (2018)
A third of packages produced worldwide are made of plastics, and food packaging is their major application, showing the largest growth in this sector when compared with other food packaging materials. The success of plastics is the result of nearly one century of successful polymer science and technology development. Polymer-based nanocomposites (PNC) are newcomers to the food packaging market in spite of the intensive research carried out during the last 20 years. This chapter reviews the manufacture processes of PNC and presents the main processing and converting technologies available for the industrial production of plastic food packages. The thermorheological properties needed for the conversion of polymers into plastic packages are highlighted with the aim to elucidate the current difficulty for PNC and biodegradable plastics to reach the market